KONVERSI ELEKTROKIMIA AMONIA MENJADI HIDROGEN - Ratnawati Ratnawati; Sumarno Sumarno; Amin Nugroho (TEKNIK, 2010)
One of the most dangerous pollutants in wastewater is ammonia. The concentration of ammonia inwastewater discharged from nitrogen fertilizer industry is up to 1500 ppm. Ammonia can be removed byseveral methods such as biological denitrification, air-stripping, and ion exchange. The methods cannotreduce the concentration of ammonia to a low level as required for standard quality of wastewater. Theelectrochemical method has recently attracted attention for the treatment of wastewater containing ammonia.This research is aimed to evaluate the effect of ammonia concentration, current density, and time on theelectrolysis process. Synthetic wastewater containing 500-1500 ppm of ammonia was used in this research.The solution was electrolyzed in a electrolytic cell with Pt/SS electrodes. The experiment was conducted byvarying current density in the range of 5 – 10 mA/cm2 and time from 0 to 105 minutes. The experiment resultsshow that as current density rises, the electrolytic reaction occurs more rapidly. On the other hand, initialconcentration of ammonia has negative effect on the final conversion of ammonia.